THE PSYCHOLOGICAL ROLE OF MOTIVATION IN STUDENTS’ LEARNING ACTIVITIES (International journal of artificial intelligence, 2026)
This article provides a scientific and theoretical analysis of the psychological role and significance of motivation in students’ learning activities. It highlights the influence of motivation on students’ cognitive activity, their attitude toward the learning process, and the effectiveness of knowledge acquisition.